Arctigenin Attenuates Tumor Metastasis Through Inhibiting Epithelial–Mesenchymal Transition in Hepatocellular Carcinoma via Suppressing GSK3β-Dependent Wnt/β-Catenin Signaling Pathway In Vivo and In Vitro - Lu, Zheng; Chang, Lingling; Zhou, Hongbo; Liu, Xiaoqiang; Li, Yinqian; Mi, Tiejun; Tong, Dewen (Frontiers in Pharmacology, 2019)
Arctigenin (ARG) has been reported to be a bioactive lignan from Arctium lappa exerting various activities including anti-cancer, immune-regulation and etc. The present study aimed to investigate the anti-metastasis activity and mechanism of ARG against hepatocellular carcinoma in vitro and in vivo. The results showed that ARG exhibited a significant cytotoxicity Hep G2 and SMMC 7721 cells (but not on normal liver cells LO2). In addition, the migration and invasion of Hep G2 and SMMC 7721 cells were also remarkably repressed. Furthermore, ARG attenuated Wnt/β-catenin signaling activation, resulted in the down-regulation of β-catenin target genes including c-Myc, Cyclin D1, MMP-9 and ZO-1. Noticeably, ARG attenuated the activation of Wnt/β-catenin through a GSK3β-dependent pathway. Besides, we also found that ARG potentially inhibited epithelial-mesenchymal transition by up-regulating the epithelial and down-regulating the mesenchymal marker proteins. In vivo, intraperitoneal injection of ARG not only significantly inhibited the growth of subcutaneous transplanted tumor, but also dramatically alleviated the tumor metastasis in liver. Our data demonstrated that ARG exerted anti-epithelial-mesenchymal transition and anti-metastasis activities against hepatocellular carcinoma, which might make it a candidate as a preventive agent for cancer metastasis.